HOMEWORK ASSIGNMENT #1 - Polgar, Michael (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Write a one-page essay (longer is acceptable), editing your work to achieve clarity and accuracy. You should use the textbook to help you with this assignment, you can draw upon your own experience, and you may also research one topic using the internet or library, as long as you cite your sources.